A Collaborative Response by Public Health and Local Hospitals to a NICU Tuberculosis Exposure. (4th October 2017) - Erme, Marguerite; Bower, John; Abell, Virginia; Bair, Tina; Rodriguez, Tracy; Kirk, Jane
Abstract: Background: Early recognition of tuberculosis (TB) cases is critical to prevent spread. Infants are at high risk for TB acquisition after exposure. A TB case went unrecognized despite seeking medical attention in December 2016 for a cough and suspicious radiographic and laboratory testing. During a two week period in November and December 2016 the case visited an infant in a Neonatal Intensive Care Unit (NICU) almost daily for extended periods of time. The NICU was housed in a local community hospital, but staffed by personnel from a separate local children's hospital. On January 3, 2017, Summit County Public Health was notified of the case and after ascertaining the potential NICU TB exposure began a collaborative contact investigation with the community hospital and the children's hospital staff, newborns and visitors to the NICU. Methods: This observational study describes a TB contact investigation of potentially exposed persons in a NICU. The three institutions jointly developed a plan whereby the children's hospital notified families of the potentially exposed babies, provided prophylactic anti-tubercular medication and follow-up screening. The hospitals' Infection Preventionists notified and tested the potentially exposed staff. The health department screened the case's family, personal contacts, and any identified or concerned NICU visitors. At the onset of the investigation the three institutions held a joint press conference. The investigation began in early January 2017 and ended late April 2017. Results: Conclusion: An after-action review revealed strengths, weaknesses and lessons learned. One successful decision was the planned press conference that provided media and public with transparent, consistent messages. A weakness was the inability to identify visitors since there was no NICU visitor log. Therefore visitors other than parents could not be individually contacted about exposure and screening. This investigation successfully involved three different community institutions and was conducted with minimal disruption and public concern. Disclosures: All authors: No reported disclosures.